PENGARUH STRES KERJA DI MASA PANDEMI COVID 19 TERHADAP KINERJA PETUGAS ADMINISTRASI DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Muhammad Firdaus; Sandya Bunga Prathivi; Agus Salim (LPPM Universitas Awal Bros, 2021)
Arifin Achmad Riau Province Hospital is one of the referral hospitals for covid 19 patients in Riau. This shows that hospitals provide services not only to general patients but also to covid 19 patients. The additional tasks that were not previously available indicate that there is work stress, especially for administrative officers because they have an important role related to hospital administration. This study aims to see the effect of work stress on the performance of officers either partially or simultaneously. The type of research is quantitative with a total sample of 46 people and the sampling technique is non probability sampling with saturation sampling method. The results of the study indicate that the Adjusted R Square is 0.681, which means that the independent variable can explain the dependent variable of 68.1% while 31.9% is explained by other factors not included in the model. The T-test shows that each variable, both Organizational Stressor and Life Stressor, has a significant effect on the performance of officers. The results of the F Test show that simultaneously Organizational Stressors and Life Stressors during the covid 19 pandemic have a significant effect on the performance of administrative officers. The suggestion that researchers recommend is that the hospital should pay attention to and manage the work stress of administrative officers, create a conducive organizational environment so that it can minimize stress, and provide education related to work stress so that officers understand and are able to manage work stress. Keywords : Work Stress, Covid 19, Performance